Childbirth fear and its associated factors among pregnant women attending antenatal care at Gondar city public health institutions, northwest Ethiopia, 2022 - Wubedle Zelalem Temesgan; Mastewal Belayneh Aklil; Tazeb Alemu Anteneh; Selam Yibeltal Desalegn (PLoS ONE, 2025)
Background Childbirth is a normal physiological process that transit women to motherhood, and it is a major event in women’s life. Women face many challenges from conception to the childbirth process and during the postpartum period. Childbirth fear is one of the problems women encounter during pregnancy and it is associated with a wide range of negative outcomes on the health of the woman and her fetus. Even though childbirth fear has had negative health outcomes studies on the prevalence and its associated factors are scares in developing countries including Ethiopia. Methods An institutional based cross-sectional study was conducted among 453 pregnant women from February 15–28/2022. Data were collected using a pretested, interviewer administered questionnaire, and a systematic sampling technique was employed to select the study participants. Epi Data version 4.6 and SPSS 25 were used for data entry, cleaning and, analysis, respectively. A binary logistic regression (bi- and multivariable) model was fitted to identify factors associated with childbirth fear. The level of significant association was declared using the adjusted odds ratio (AOR) with its 95% confidence interval (CI) and a p-value of ≤ 0.05. Results Childbirth fear among pregnant women was 23.8% (95% CI: 20.1–28.0). Being rural residence (AOR = 6.24, 95% CI: 3.05, 12.80), having moderate social support (AOR = 0.54, 95% CI: 0.29, 0.99), anxiety during pregnancy (AOR = 2.82, 95% CI: 1.52, 5.23), and intimate partner violence (AOR = 4.95, 95% CI: 2.78, 8.81), were significantly associated with childbirth fear. Conclusion The study showed that the magnitude of childbirth fear is high in the study area. Policymakers should develop strategies or screening tools for the early identification of women with pregnancy-related anxiety and childbirth fear, and it is important to give special attention and counseling to pregnant women in rural areas and victims of intimate partner violence.